Entrepreneurship Education and Environmental Awareness as Catalysts for Green Entrepreneurial Intention: A Self-Efficacy Perspective - Damas Gianlugi Alrizqi; Mildayanti Mildayanti; Agung Muliaman Anas; Nurul Haeriyah Ridwan; Moch Faizal Rachmadi (Jurnal Penelitian Pendidikan, 2026)
This study analyzes the influence of entrepreneurship education and environmental awareness on students' green entrepreneurial intention, with green entrepreneurial self-efficacy as the mediator. Data were collected through a survey of 150 university students in Makassar using a 1–5 Likert scale and analyzed using SEM-PLS (WarpPLS). The results show that entrepreneurship education and environmental awareness positively affect green entrepreneurial self-efficacy, and that self-efficacy positively affects green entrepreneurial intention. In addition, self-efficacy has been shown to mediate the effects of entrepreneurship education and environmental awareness on green entrepreneurial intention. The findings emphasize the importance of strengthening students' self-confidence through entrepreneurship learning and integrating sustainability issues into campus programs.